Identification and characterization of two Croquemort homologues in penaeid shrimp Litopenaeus vannamei. Issue 60 (January 2017) - Hou, Fujun; Liu, Tao; Wang, Qiai; Liu, Yongjie; Sun, Chengbo; Liu, Xiaolin
Abstract: Croquemort, the homologue of human CD36, is a member of class B scavenger receptors, which is involved in bacteria phagocytosis and cytokins release. However, there is still less information about Croquemort in crustaceans. Here, a Croquemort from Pacific white shrimp Litopenaeus vannamei ( Lv Croquemort) and its truncated form ( Lv Croquemort-S1) cDNA sequences were identified, characterized and their role in bacteria clearance was investigated. The deduced protein of Lv Croquemort is 533 amino acids and contains typical domains of CD36: the N-terminus and C-terminus in cytoplasm, two transmembrane regions and a large extracellular loop-like domain. However, Lv Croquemort-S1 losses partial cDNA sequence in its middle and its deduced protein losses the C-terminal transmembrane region and C-terminus in cytoplasm, the latter of which is found participating in cytokins release in human CD36. Lv Croquemort transcript is highly expressed in gills, hemocytes, testis and slightly in heart, hepatopancreas and nerve. Besides, its responses to bacteria Vibrio anguillarum and white spot syndrome virus were examined. Knock-down of Lv Croquemort by specific dsRNA reduces bacteria clearance. These initial data will help to further understand roles of Croquemort in crustacean innate immunity. Highlights: Two Croquemort homologues were identified and characterized in penaeid shrimp Litopenaeus vannamei. Its responses to bacteria Vibrio anguillarum and white spot syndrome virus were examined. RNAi knock-down of Lv Croquemort reduced bacteria clearance.